2011
DOI: 10.1155/2011/713281
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia in Trauma Medicine

Abstract: Regional anesthesia is an established method to provide analgesia for patients in the operating room and during the postoperative phase. While regional anesthesia offers unique advantages, as shown by the recent military experience, it is not commonly utilized in the prehospital or emergency department setting. Most often, regional anesthesia techniques for traumatized patients are first utilized in the operating room for procedural anesthesia or for postoperative pain control. While infiltration or single ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 26 publications
0
24
0
2
Order By: Relevance
“…2009, Wu et al. 2011). Since these incidents, no regional anesthesia has been used in tibial osteotomies—either in children or in adults—at our department.…”
Section: Discussionmentioning
confidence: 99%
“…2009, Wu et al. 2011). Since these incidents, no regional anesthesia has been used in tibial osteotomies—either in children or in adults—at our department.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that compartment syndrome can be safely detected despite functional regional blockade 55 and pa- ). The French Society of Anaesthesia does not consider the risk of ACS as a contraindication for regional anesthesia 56 and because there is evidence that regional blockade can increase the blood flow through the partial sympathetic blockade without blocking the warning signs of ACS, the implementation of regional anaesthesia also in patients in the risk of ACS should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…One of the primary advantages of preoperative regional anesthesia is the reduction of required intravenous opioid to relieve pain (Wu, Lollo, & Grabinsky, 2011). Recent research has found opioids to have some deleterious effects.…”
Section: Innovations In Pain Managementmentioning
confidence: 99%